SISTEM INFORMASI MANAJEMEN PEMASARAN TV KABEL BERBASIS WEB PADA PT IRAMA TV - Bagus Sujiwo; Efrizon Efrizon (Universitas Negeri Padang, 2019)
Progress The development of information technology (IT) is increasingly rapid both for the use of software (software) and hardware (hardware) which is increasingly easy to use (user friendly) to help learning all the users of information technology. In the world of education or everyday life everyone needs to get entertainment or reference that must be used to be a reference so that they are not bored and bored after a day of tired activities. One of them can be done by watching through the internet network television media or TV (Cable) subscription TV. This cable TV management information system is designed using a web-based prototyping method involving the PHP (PHP Hypertext Preprocessor) programming language based on the code -iter, JavaScript, Jquery framework. While the database used is MYSQL. In system design is involved Use Case, Activity Diagram, Context Diagram, Flowmap, Sequence Diagram and ERD. This system also uses aliases on its addressing by applying htaccess to the actual file address as one of the security systems. . This information system involves six admin users, customers, leaders, finance, officers and marketing. The six levels of registered users have a private account to be able to enter the system ie username and password with MD5 encryption. Because it is web-based, this cable TV application has the ability, can be accessed anywhere, admin can do add, edit, delete and store customer data and customer transaction data, and can print reports.